Pengaruh Pembelajaran Kitab Akhlak Lil Banin Terhadap Prilaku Sopan Santri di Pondok Pesantren Walisongo Lampung Utara - Hidayah, Ridho (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research examines the learning of the Lil Banin Book of Morals on the polite behavior of students at the Walisongo Islamic boarding school, North Lampung. It is hoped that this learning can instill morals in students who are older and younger than them through the book Morals of Lil Banin. This study uses a qualitative method. The data collection methods used were observation, interviews and documentation. The aim of this research is to instill Santri Morals in older and younger people through learning the Lil Banin Book of Morals at the Walisongo Islamic boarding school. The Lil Banin Book of Morals Study Method uses the bandongan method, lectures, habituation methods, example and advice. The moral material for students contained in the Book of Morals of Lil Banin for students at the Walisongo Islamic Boarding School focuses on the moral material for older and younger students. The study of Lil Banin's Book of Morals to instill morals in students among older and younger students has been quite good and is going well, and most of the students have implemented appropriate morals in their daily lives. The results of the study of Lil Banin's Book of Morals show several successes, namely the occurrence of significant changes in the morals of the students, these changes can be seen from changes in behavior in the students, such as reducing the level of violations of boarding school rules, prioritizing manners when meeting someone older, and being honest. , and what they have been taught and learned they have applied in their daily lives in accordance with the study of the Book of Morals of Lil Banin.